EFIKASI INSEKTISIDA NABATI EKSTRAK BUNGA KEMBANG BULAN (Tithonia diversifolia A. Gray) TERHADAP HAMA ULAT GRAYAK (Spodoptera litura F.) PADA TANAMAN SAWI DI LABORATORIUM - Azwana, Azwana; Mardiana, Siti; Zannah, Rizky Raudatul (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2019)
Armyworm (Spodoptera litura) is one of the pests that attack vegetable plants in Indonesia. The attack resulted in the leaves of the plant being cut and perforated so as to reduce productivity and even crop failure The aim of the study was to determine effectiveness of Tithonia diversifolia extract as a vegetable insecticide to control the Spodoptera litura in mustard plants at the laboratory. The study used a completely non-factorial randomized design consisting of 5 treatments, K0 = no extract (control), K1 = concentration 4%, K2 = concentration 6%, K3 = concentration 8%, K4 = concentration 10%. Parameters observed were morphological changes and insect behavior, percentage of larval mortality, percentage of pupae and imago formed. The results that Tithonia diversifolia extract can control Spodoptera litura. The result of 8% (K3) Tithonia diversifolia extract effectively controls Spodoptera litura. The highest percentage of larval mortality of Spodoptera litura (80%) was found in the treatment of K3 (concentration 8%) at observation 9 HSA and the lowest mortality was found in K1 (concentration 4% with an average 67.5%. The lowest formation of pupa and imago in the K3 treatment was 20 and 29.17%